Implementasi Model Pembelajaran Kooperatif TSTS dalam Meningkatkan Hasil Belajar - Aay Farihah Hesya; Dea Santi Yuliani (Sekolah Tinggi Agama Islam Persatuan Umat Islam Majalengka, 2026)
This research stems from an initial observation indicating low learning outcomes among seventh-grade students at MTs Darul Falah Cijati in Akidah Akhlak (Islamic Creed and Morality) subject, particularly concerning the reprehensible morality material of Riya' (showing off) and Nifaq (hypocrisy). This material, which inherently demands deep understanding and internalization of affective values, is often taught conventionally, leading to a lack of student motivation and shallow conceptual comprehension. This condition necessitates an innovation in teaching methods to create a more interactive, collaborative, and effective learning environment. Therefore, this study aims to investigate the extent to which the implementation of the Two Stay Two Stray (TSTS) cooperative learning model can significantly improve students' learning outcomes on the Riya' and Nifaq material. The method used in this research is Classroom Action Research (CAR), conducted in two cycles at MTs Darul Falah Cijati, with 24 seventh-grade students as subjects. Each CAR cycle was systematically designed through four stages: planning of learning actions, implementation of actions in the classroom, observation of the process and student responses, and reflection for evaluation and improvement in the subsequent cycle. Data collection instruments included learning outcome tests and documentation.The research results show a consistent and significant improvement in students' learning outcomes from Cycle I to Cycle II. In Cycle I, the average learning outcome score was 69.17, with a classical mastery level reaching 62.5%. This indicated that some students had not yet met the minimum mastery criteria. After improvements and more optimal action implementation in Cycle II, the average score increased to 76.88, with the classical mastery level significantly rising to 79.17%. This increase not only reflects a better conceptual understanding but also demonstrates that the application of the TSTS learning model can help students understand the material more effectively and foster cooperation among students. Thus, it can be concluded that the implementation of the Two Stay Two Stray (TSTS) cooperative learning model is effective in improving students' Akidah Akhlak learning outcomes on the reprehensible morality material of Riya’ and Nifaq.